2011
DOI: 10.1266/ggs.86.151
|View full text |Cite
|
Sign up to set email alerts
|

trans-translation-mediated tight regulation of the expression of the alternative ribosome-rescue factor ArfA in Escherichia coli

Abstract: Ribosomes translating mRNA without an in-frame stop codon (non-stop mRNA) stall at its 3' end. In eubacteria, such ribosomes are rescued by SsrA-mediated trans-translation. Recently, we have shown that Escherichia coli ArfA (formerly YhdL) also rescues stalled ribosomes by a mechanism distinct from that of transtranslation. Synthetic lethality phenotype of ssrA arfA double mutants suggests that accumulation of stalled ribosomes is deleterious to E. coli cells. In this report, we show that the expression of Arf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
73
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(79 citation statements)
references
References 36 publications
(41 reference statements)
6
73
0
Order By: Relevance
“…This suggests conformational disorder of the C-terminus at the entrance to the mRNA tunnel. Our structures are consistent with biochemical studies (Chadani et al, 2011), which showed that ArfA is functional with a C-terminal truncation at Asn47, but further shortening inactivates ArfA. In particular, truncations following Met40—removing at least five basic amino acids that bind in the tunnel—abrogate ArfA-mediated release by reducing ArfA affinity for the 70S ribosome (Chadani et al, 2011).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…This suggests conformational disorder of the C-terminus at the entrance to the mRNA tunnel. Our structures are consistent with biochemical studies (Chadani et al, 2011), which showed that ArfA is functional with a C-terminal truncation at Asn47, but further shortening inactivates ArfA. In particular, truncations following Met40—removing at least five basic amino acids that bind in the tunnel—abrogate ArfA-mediated release by reducing ArfA affinity for the 70S ribosome (Chadani et al, 2011).…”
Section: Resultssupporting
confidence: 89%
“…[Keiler, 2015]). The ArfA ( a lternative r escue f actor A ) pathway is essential in trans-translation-deficient cells (Chadani et al, 2010) and is thought to function as a backup mechanism for trans-translation in enterobacteria (Garza-Sánchez et al, 2011; Chadani et al, 2011; Schaub et al, 2012). ArfA is a small protein (~70 aa in most organisms), with only 47 amino acids sufficient for function, as shown for E. coli ArfA truncations (Garza-Sánchez et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The levels of synthesis of the ArfA protein (assessed by ribosome occupancy) are more than 80-fold increased. Interestingly, ArfA expression is regulated by tmRNA in an elegant feedback mechanism such that when the capacity of tmRNA is exceeded, ArfA accumulates (29,30). The fact that ArfA is strongly upregulated in cells treated with RelE suggests that the tmRNA system is overwhelmed and that cells are responding to the need for more ribosome rescue activity by upregulating ArfA expression.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the expression of ArfA is tightly regulated by the system involving transtranslation. 21 This suggests that the ArfAdependent system may play a backup role to the tmRNA-dependent system. Additionally, the tmRNA rescue system is linked to the SspB-ClpXP protein degradation system for the maintenance of the quality of cellular proteins, 10 which suggests a more prevailing role for the tmRNA rescue system in the translation maintenance.…”
Section: Discussionmentioning
confidence: 99%